ANALISIS PENGARUH LABEL HALAL DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MAKANAN CEPAT SAJI MAHASISWA UNIVERSITAS SULTAN AGENG TIRTAYASA PROGRAM STUDI EKONOMI SYARIAH ANGKATAN 2023 - Ihsan, Rifqi Fatihul; Istiyah, Aiska Su; Arifin, Arifin; Laki, Nur Sasti (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2024)
This study was discussed to analyze the effect of halal label and price on fast food purchasing decisions of Sultan Ageng Tirtayasa University student class of 2023. The gender and class background of students who are divided into study programs make respondents pay attention to aspects of halal labels and prices in making decisions on choosing fast food products. The population in this study were students of Sultan Ageng Tirtayasa University with the Sharia Economics study program class of 2023. The data used is primary data using a questionnaire and distributed to respondents and resulted in 84 respondents. The sampling technique used was purposive sampling technique. This research is quantitative research with data analysis methods using multiple linear regression. The results showed that the halal label and price had an effect on fast food purchasing decisions where the value of the multiple linear regression test results (R) was 51.3%, which means that 51.3% of the variation in the decision to buy fast food paid attention to 2 supporting variables, namely, Halal Label (X1) and Price (X2). While the remaining 48.7% is approved by other variables not included in this study.